Rabies control and elimination: a test case for One Health. (30th August 2014) - Cleaveland, Sarah; Lankester, Felix; Townsend, Sunny; Lembo, Tiziana; Hampson, Katie
Abstract : One Health approaches have already been shown to be successful in controlling rabies in different parts of the world. In this article, the latest in Veterinary Record' s series promoting One Health, Sarah Cleaveland and her colleagues at the University of Glasgow discuss why integrated strategies are needed to enhance the cost effectiveness of measures to control and eliminate rabies, particularly in low‐income countries